WANPRESTASI DAN AKIBATNYA DALAM PELAKSANAAN PERJANJIAN - Muhammad Riandi Nur Ridwan; Yana Sukma Permana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
Agreement by the parties as a basis for the legal relationship of the agreements that have been approved, which give rise to rights and obligations of the parties. With the expected agreement all of what has been agreed to function normally, but in practice in certain circumstances the exchange of achievement does not always work as it should so that it appears what is called a default. Default is: